Soluble E-Cadherin: An Early Marker of Severity in Acute Pancreatitis. (27th April 2009) - Sewpaul, A.; French, J. J.; Khoo, T. K.; Kernohan, M.; Kirby, J. A.; Charnley, R. M.
Abstract : Background/Aims . At present, there is no simple test for predicting severity in acute pancreatitis. We investigated the use of an assay of soluble E-cadherin (sE-cadherin). Methods . Concentrations of sE-cadherin, from 19 patients with mild acute pancreatitis, 7 patients with severe acute pancreatitis, 11 patients with other acute gastrointestinal pathologies, and 12 healthy subjects were measured using a commercially available sandwich ELISA kit based on two monoclonal antibodies specific to the extracellular fragment of human E-cadherin. Measurements were made at 12 hours or less from onset of pain and also at 24 and 48 hours after onset of pain. Results . Mean (standard deviation) concentration of sE-cadherin in patients with severe acute pancreatitis at< 12 hours was 17780 ng/mL (7853), significantly higher than that of healthy volunteers 5180 ng/mL (1350), P = .0039, patients with other gastrointestinal pathologies 7358 ng/mL (6655), P = .0073, and also significantly higher than that of patients with mild pancreatitis, 7332 ng/mL (2843), P = .0019 . Discussion . Serum sE-cadherin could be an early (within 12 hours) objective marker of severity in acute pancreatitis. This molecule warrants further investigation in the form of a large multicentre trial.